PROFESSIONAL DEVELOPMENT OF NOVICE TEACHERS: A REVIEW OF INTERNATIONAL EXPERIENCE - Кереева, Оксана; Yegenissova , Almazhai; Bayar, Adem (Pedagogy and Psychology, 2025)
The professional development of novice teachers plays a crucial role in shaping educational quality and student outcomes. This study examines teacher preparation and professional development systems in highperforming education systems, focusing on mentoring, structured induction, and career progression. Using a comparative approach, the research analyzes the distinct strategies employed in different national contexts and identifies key elements that contribute to teacher effectiveness and retention. The study highlights the importance of combining academic training with practical experience, ensuring rigorous selection criteria, and providing sustained professional support for novice teachers. The findings offer insights into best practices that can be adapted to improve teacher development policies, particularly in education systems undergoing reform. By contextualizing international models, this study contributes to the broader discourse on teacher education and provides evidence-based recommendations for strengthening teacher professional development. The research underscores the need for systematic and sustainable approaches to enhance teacher preparedness, ultimately supporting long-term improvements in teaching quality and educational outcomes. The system of professional development of novice teachers in foreign countries has its conceptual features determined by the relevant contextual factors. Such an approach can increase the professionalism of novice teachers, and their ability to provide students with high-quality and effective teaching by the needs of the market economy. Comparing the experience of various countries with the current state of teachers' professional development system in Kazakhstan, the article offers some recommendations for integrating successful practices into the Kazakh educational environment. It is concluded that to ensure the high quality of education in Kazakhstan, a systematic approach to the professional development of novice teachers is needed, based on the best world practices.